If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + 4) = 10 Reorder the terms: -1(4 + x) = 10 (4 * -1 + x * -1) = 10 (-4 + -1x) = 10 Solving -4 + -1x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 10 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 10 + 4 -1x = 10 + 4 Combine like terms: 10 + 4 = 14 -1x = 14 Divide each side by '-1'. x = -14 Simplifying x = -14
| 3+4x=2x-9 | | -5(X+2)=5 | | 5(2-a)=a-8 | | 0.95x+75=360 | | g=20s+1*1.5 | | 3m+5.25=33.75 | | -3+Y=-2 | | 6t+3c+3f+4t+2c+3f= | | 69a*3x=29ax-100p | | 4r=2y-2b | | 3m+7.75=36.25 | | 4(x+3)=48 | | 3r=3y-5b | | 4x-3y=12 | | 4(2x-1)=4 | | 2x-26=14 | | 4(x-1)=4 | | 4(x-1)=-12 | | 2(x+7)=34 | | -3(x+1)=6 | | 4(x-1)=12 | | -2(x-7)=16 | | 0+Y=-3 | | 8x^2-8x-30=0 | | -6+Y=-3 | | 2(3x+2)=52 | | 12b+14+10b=80 | | 2=5m-3 | | 4x+33=2x+57 | | 5x-14=84-5x | | 7x+3=3x+27 | | 2h+9=10 |